Modelo para la mejora del servicio de atención al cliente mediante la teoría de colas: caso de estudio de una agencia bancaria - León Lazo, Leticia Siu Leng (2023)
This article analyses waiting lines at a bank branch where customers described long queues and waiting time (8,539 minutes on average) as the main problem with the bank's service. For research purposes, we modeled a system, based on queueing theory, in Arena software (16.1 Student Version) to identify possible improvements to customer service. The waiting line simulation considered resources, waiting times, time between arrivals, and entities involved. We gathered data using an explanatory and descriptive quantitative approach. The proposed model offered positive results, such as a 52,61 % reduction in queue time. The model also allowed us to identify different factors affecting queue time, such as customers who do not finish the process and leave because they did not comply with all the requirements for a given service. The proposed improvement also helps to reduce the number of people who withdraw from the process from 14,52 % to 4,032 %. Different variables that determine poor customer service reviews despite shorter waiting time limits the results obtained.